Examining Perang Topat in Lombok: The Intersection of Islamic Education, Cultural Tradition, and Social Harmony - Muliadi, Erlan; Abd. Karim, Aishah Hanim; Nasri, Ulyan (Didaktika Religia, 2024)
This research examines the historical and cultural aspects of the Perang Topat ritual in Lombok, Indonesia, with a particular focus on the role of Islamic education in the preservation of this local tradition. This study examines the impact of Islamic teachings on the ritual, elucidating the interconnection between religion and culture. The study employs a qualitative methodology, encompassing ethnographic fieldwork, interviews and document analysis with key informants, including religious leaders and cultural practitioners. The findings indicate that Perang Topat is reflective of cultural and religious diversity, with participation from both Muslim and Hindu communities. The ritual is firmly embedded in the historical context of an agrarian society and serves to promote values of gratitude, togetherness and mutual respect. It can be seen that Islamic education plays a pivotal role in influencing the younger generation’s comprehension of the ritual and in guaranteeing its cultural significance is maintained. While this research is focused on a single cultural site, further studies in other regions could extend these findings and provide deeper insights into the interplay between religion and tradition in Muslim communities.